(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the formation of written and speech competence among students of Uzbek groups of the non-philological faculty and the peculiarities of linguistic factors in teaching writing. The methodology of teaching English is closely related to linguistic science, since linguistics is one of the fundamental sciences for the methodology of teaching a foreign language. The methodology receives educational material from linguistics. The content and nature of the English language studied at a university is determined by the linguistic characteristics of the native (Uzbek) and foreign (English) languages. Lingvodidactic comparative analysis is of a diagnostic nature, it is possible to identify the difficulties that arise in teaching written speech, to determine and scientifically substantiate the reasons for their occurrence. A differential approach to determining the characteristic properties of writing and written speech based on the dichotomy of language and speech greatly contributes to a deeper understanding of the relationship between writing and written speech. Methodologists related to the problems of language teaching to determine the correct choice of language means, methods, methods, techniques and forms of organizing the educational process, aimed at developing written and speech professional competencies among students of a non-philological university.